2016
DOI: 10.1088/0031-9155/61/2/958
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric impact of the low-dose envelope of scanned proton beams at a ProBeam facility: comparison of measurements with TPS and MC calculations

Abstract: Due to the low-dose envelope of scanned proton beams, the dose output depends on the size of the irradiated field or volume. While this field size dependence has already been extensively investigated by measurements and Monte Carlo (MC) simulations for single pencil beams or monoenergetic fields, reports on the relevance of this effect for analytical dose calculation models are limited. Previous studies on this topic only exist for specific beamline designs. However, the amount of large-angle scattered primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
(47 reference statements)
5
17
1
Order By: Relevance
“…In a study by Lee, it was found that, provided the spot spacing was equal to or smaller than two‐thirds of the spot size (FWHM), a plan with 100% uniformity could be achieved. It has been shown previously that spot spacing has an impact on the field sizes . This was not found in our work, with the extent of spot positions remaining within the field sizes as expected, however, an optimal spot spacing should be found to balance dose homogeneity with output factor for a given field size …”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In a study by Lee, it was found that, provided the spot spacing was equal to or smaller than two‐thirds of the spot size (FWHM), a plan with 100% uniformity could be achieved. It has been shown previously that spot spacing has an impact on the field sizes . This was not found in our work, with the extent of spot positions remaining within the field sizes as expected, however, an optimal spot spacing should be found to balance dose homogeneity with output factor for a given field size …”
Section: Discussionsupporting
confidence: 58%
“…It has been shown previously that spot spacing has an impact on the field sizes . This was not found in our work, with the extent of spot positions remaining within the field sizes as expected, however, an optimal spot spacing should be found to balance dose homogeneity with output factor for a given field size …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…These measurements have previously been reported for an IBA PBS nozzle . Wurl et al used ion chambers for measurement and validated a FLUKA Monte Carlo (MC) simulation to model the halo effect for a Varian ProBeam system . The results obtained by Wurl et al were used to influence analytical dose calculations.…”
Section: Introductionmentioning
confidence: 91%
“…However, Monte Carlo algorithms do not model the halo that is created upstream from the treatment volume, for example, in a range shifter . This can lead to discrepancies for low‐energy proton beams as the halo is generated in both the treatment head and through scattering in air . In commissioning our Varian ProBeam PBS system, we found the largest disagreement between TPS and measurement was 8% for a 2 × 2 cm 2 monoenergetic field at 70 MeV.…”
Section: Introductionmentioning
confidence: 99%